EFEKTIVITAS COGNITIVE RESRUCTURING DALAM KONSELING KELOMPOK UNTUK MENINGKATKAN RESLIENSI AKADEMIK SISWA SMA - Dimas Ardika Miftah Farid; Rini Undiarti (INSIGHT: Jurnal Bimbingan Konseling, 2026)
This study aims to examine the effect of group counseling using cognitive restructuring techniques on students’ resilience to academic stress. This study adopted a quantitative approach with a single group pretest posttest experimental desig. The study population consisted of all XII grade student Wachid Hasyim 5 Surabaya High School, with a sample of six students selected based on the results of the academic resilience pretest with low and moderate categories. The data collection instrument used an academic resilience scale. The data analysis technique used the Wilcoxon Signed Ranks Test. The results of the study showed an increase in students' academic resilience scores from the pretest to the posttest. In the pretest, students' academic resilience was in the low and moderate categories, while in the posttest, most students were in the high category. Therefore, it can be concludedthat group therapy services using cognitive restructuring techniques have a significant influence in increasing students’ academic resilience.